Science and technology human resource capacity for economic growth: The case of Korea - Park, Myungsoo (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This paper presents the policies Korea adopted to educate and train scientists/researchers and technicians/skilled workers. The Korean policies for the increase of human resources in science and technology that stimulated an upgrading of skills in industry and adapted to technical advancements are identified. An important factor is that the supply and demand mechanism created a virtuous circle so that the science and technology education and training policies were responsive to economic demands. In addition, policies to foster a human resource capacity have enhanced the contribution of human resources in science and technology for innovation and economic growth.